SINTESIS DAN UJI TOKSISITAS SENYAWA ANALOG KURKUMIN 3,5 BIS((E)-METOKSI BENZILIDEN)-1-(2-ETIL ASETAT)-PIPERIDIN-4-ON - Aisyah, Siti; Zamri, Adel; Teruna, Hilwan Yuda (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2018)
Curcumin analogs are secondary metabolites and belong to the phenolic group. These compounds have biological activities, such as anti-inflammatory, anticancer and antioxidant. This studies has successfully synthesized 3,5-bis ((E)-metoxy benzylidene) -1-(- 2-ethyl acetate) piperidine 4-one analog compound from 4-piperidone with 4-methoxy benzaldehyde by using reflux method. Compounds obtained in the form of yellow solids with yield 83.01%. The melting point was measured, identified by TLC then elucidated with UV-Vis, FT-IR, LC-MS, 1H NMR obtained results showed that the curcumin compound had a structure in accordance with the target molecule. The toxicity test using the BSLT method showed that the two compounds had LC50 values = 1.061Î¼g / mL.